Comparison of Treatment Modalities for Management of Pain in Pediatric Gartland Type I Extension Type Supracondylar Humerus Fractures Using Above Elbow Backslab (Splint Immobilization) Versus Collar and Cuff - Umer, Yasir; Ismail, Syed Junaid; Nisar, Amir; Umer, Waleed; Junaid, Nadia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of the above elbow backslab versus collar and cuff sling to treat Gartland Type I supracondylar fracture in terms of better pain control.Study Design: Quasi experimental study.Place and Duration of Study: Department of Orthopedic Surgery, Federal Government Polyclinic Hospital, Islamabad, Pakistan, from Jan 2020 to Jan 2021.Methodology: The study enrolled a total of 60 pediatric patients who suffered from extension type Gartland Type I supracondylar fracture, with 30 patients allocated to one of two groups. In Group A, the fracture was managed by using above elbow backslab and in Group B, the collar and cuff sling was utilized. Post-treatment pain evaluation at the fracture site was done using the Visual Analogue Scale (VAS).Results: The mean age of the patients was 7.35±1.94 years, comprising of 37(61.7%) males and 23(38.3%) females. Significant pain (VAS ≥4) was present in 4(13.3%) patients from Group A and 15(50%) patients from Group B, which was noted to be statistically significant (p-value=0.02).Conclusion: Management of Supracondylar fracture Gartland Type I with above elbow backslab was associated with less incidence and decreased severity of pain as compared to management by collar and cuff.